Unit Cost Calculation of Elective Caesarean section without Complications Based on The Time-Driven Activity-Based Costing Model - Destania Tri Kusuma Wardani; Firman Pribadi (Universitas Aisyah Pringsewu, 2023)
The unit cost calculation method of services in hospitals is fundamental because its inaccuracy of its can lead to differences in the final result of the total service tariff. A private hospital in Yogyakarta is a special type C Mother and Child Hospital. This hospital service hasn’t implemented unit cost, so the tariff system for patients is vaguely based on hereditary rates from the owner. The research design used was qualitative, with a case study method approach. The subject was elective Caesarean Sectio (CS) surgery patients without complications. The object was to all activities in a series of elective CS surgery without complications from the patient's initial admission until the patient could go home. The research instrument used a data collection form and interview guidelines. Data analysis used the TDABC calculation method. Qualitative analysis of interview results was conducted by reduction, presentation, analysis, and concluding the data. The results of the analysis’s CS unit cost used the TDABC model of 4,421,217.04 IDR. The difference between INA-CBG's claims and the CS’s unit cost used the TDABC model of 553,983 IDR (11%).Abstrak: Metode perhitungan biaya satuan pelayanan di rumah sakit merupakan hal yang mendasar karena ketidak tepatan dapat menyebabkan perbedaan hasil akhir dari total tarif pelayanan. Rumah Sakit Swasta di Yogyakarta adalah Rumah Sakit Khusus Ibu dan Anak tipe C. Pelayanan rumah sakit ini belum menerapkan unit cost, sehingga sistem tarif untuk pasien samar-samar berdasarkan tarif turun temurun dari pemiliknya. Desain penelitian yang digunakan adalah kualitatif, dengan pendekatan metode studi kasus. Subjek adalah pasien operasi Caesar elektif (CS) tanpa komplikasi. Objeknya adalah semua kegiatan yang terjadi dalam rangkaian operasi CS elektif tanpa komplikasi sejak pasien masuk sampai pasien bisa pulang. Instrumen penelitian menggunakan formulir pengumpulan data dan pedoman wawancara. Analisis data menggunakan metode perhitungan TDABC. Analisis kualitatif hasil wawancara dilakukan dengan reduksi, penyajian, analisis, dan penyimpulan data. Hasil analisis biaya satuan CS menggunakan model TDABC sebesar Rp 4.421.217,04. Selisih antara klaim INA-CBG dengan unit cost CS menggunakan model TDABC sebesar Rp 553.983 (11%).